2019
DOI: 10.1021/acscentsci.9b00706
|View full text |Cite
|
Sign up to set email alerts
|

Trapping and Electron Paramagnetic Resonance Characterization of the 5′dAdo Radical in a Radical S-Adenosyl Methionine Enzyme Reaction with a Non-Native Substrate

Abstract: S-Adenosyl methionine (SAM) is employed as a [4Fe-4S]-bound cofactor in the superfamily of radical SAM (rSAM) enzymes, in which one-electron reduction of the [4Fe-4S]-SAM moiety leads to homolytic cleavage of the S-adenosyl methionine to generate the 5′-deoxyadenosyl radical (5′dAdo•), a potent H-atom abstractor. HydG, a member of this rSAM family, uses the 5′dAdo• radical to lyse its substrate, tyrosine, producing CO and CN that bind to a unique Fe site of a second HydG Fe–S cluster, ultimately producing a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 44 publications
(103 reference statements)
0
55
0
Order By: Relevance
“…Human viperin is shown to be a member of the radical‐SAM superfamily of enzymes, which catalyse the transformation of a substrate by using a common catalytic step (Figure A): a highly conserved [4 Fe−4 S] cluster, which is coordinated to three cysteine residues of a conserved CxxxCxxC motif, cleaves SAM in a one‐electron reduction step to generate a 5′‐deoxyadenosyl radical (5′‐dAdo radical) intermediate . The 5′‐dAdo radical has recently been trapped and characterised, and spectroscopic studies have provided evidence for the formation of an organometallic intermediate with a Fe‐[5′‐C]‐deoxyadenosyl bond (Figure A) . The organometallic or the 5′‐dAdo radical intermediate initiates catalytic transformation by abstracting a hydrogen atom from a substrate, releasing 5′‐deoxyadenosine (5′‐dA), and generating a substrate–radical intermediate that undergoes complex rearrangement reactions to form a product .…”
Section: Resultsmentioning
confidence: 99%
“…Human viperin is shown to be a member of the radical‐SAM superfamily of enzymes, which catalyse the transformation of a substrate by using a common catalytic step (Figure A): a highly conserved [4 Fe−4 S] cluster, which is coordinated to three cysteine residues of a conserved CxxxCxxC motif, cleaves SAM in a one‐electron reduction step to generate a 5′‐deoxyadenosyl radical (5′‐dAdo radical) intermediate . The 5′‐dAdo radical has recently been trapped and characterised, and spectroscopic studies have provided evidence for the formation of an organometallic intermediate with a Fe‐[5′‐C]‐deoxyadenosyl bond (Figure A) . The organometallic or the 5′‐dAdo radical intermediate initiates catalytic transformation by abstracting a hydrogen atom from a substrate, releasing 5′‐deoxyadenosine (5′‐dA), and generating a substrate–radical intermediate that undergoes complex rearrangement reactions to form a product .…”
Section: Resultsmentioning
confidence: 99%
“…The X-ray structure of a related rSAM tryptophan lyase NosL included a tryptophan oriented to favor 5 0 dAdoc H-atom abstraction from this amino acid's amino group, and the authors suggested that a similar amino H-atom abstraction drives the tyrosine fragmentation in ThiH and HydG. 45 Sayler et al 46 studied the HydG reaction with a non-native substrate, 4hydroxy phenyl propanoic acid (HPPA) ( Fig. 3B), where a simple C(2)H 2 replaces the C a H-NH 2 of tyrosine.…”
Section: Hydg and The Radical Mechanism Of Tyrosine Lysismentioning
confidence: 99%
“…Thus it is clear it is the amino group of the tyrosine that is the target of the H-atom abstraction by 5 0 dAdoc, generating a transient, and yet to be observed, nitrogen centered tyrosine radical that rapidly fragments to form the DHG and 4-oxidobenzyl radical products of the rSAM component of HydG. Interestingly, when the more oxidized cis-p-coumaric acid was employed in place of HPPA, Sayler et al 46 were able to trap the primary 5 0 dAdoc which is accumulated because it cannot abstract the hydrogen atom from the sp 2 -carbon.…”
Section: Hydg and The Radical Mechanism Of Tyrosine Lysismentioning
confidence: 99%
“…In this issue of ACS Central Science , Sayler and co-workers disclose the direct trapping and characterization of the elusive 5′dAdo· radical within the confines of the hydrogenase-cofactor maturase enzyme HydG. 2…”
mentioning
confidence: 99%
“…Tyrosine lysis affords diatomic CO and CN – ligands that are components of the H cluster of di-iron hydrogenases. (B) Freeze quenching assay mixtures of HydG with the non-native substrates explored by Sayler 2 yield distinct EPR signals (right) that are assigned to the corresponding radical species. EPR signals are reproduced with permission from ref (2).…”
mentioning
confidence: 99%